Semantic Analysis of Refusal Expressions in Daily English Conversations - Rimtahi Marbun; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study explores the semantic features of refusal expressions in English daily conversations, focusing on how meaning is constructed through direct and indirect strategies. Drawing on recent developments in speech act theory, politeness theory, and sociopragmatic research, this study analyzes a variety of refusal forms that reflect both linguistic choices and social considerations. The data, compiled through qualitative library research and drawn from authentic conversational contexts, reveal that refusals often include hedges, modal verbs, and mitigating elements such as apologies or compliments. These features help soften the illocutionary force of refusal and preserve the hearer’s face. Semantic structures such as conditional clauses, discourse markers, and implicatures are commonly employed to encode indirectness, empathy, and politeness. The findings underscore how refusal expressions operate not merely as rejections but as context-sensitive speech acts shaped by cultural norms, social roles, and speaker intent.